ABUSE OF VILLAGE FUND (VF) IN INDONESIA: CASE STUDY OF VF CORRUPTION IN EAST JAVA - Siregar, Rachmi Kurnia; Aminudin, Amin (PEOPLE: International Journal of Social Sciences, 2020)
The Indonesian government in the JokoWidodo-JusufKalla era (2014-2019) accelerated welfare in the village by launching the Village Fund (VF) program in accordance with Law Number. 6 of 2014 concerning Villages. However, since the VF was rolled out in 2015, cases of misuse of funds have continued to spread, mostly involving village heads and village officials. To minimize irregularities in the VF, the Ministry of Villages from Disadvantaged Regions and Transmigration (Ministry of PDTT) established the Village Fund Task Force (VFTF) at the central level. Responding to the high case of corruption in the VF, there are two objectives in this research, namely analyzing the communication policy of the Ministry of PDTT organization by forming VFTF, as well asanalyzing ccommunication on Village Fund organizations in Dasok Village and constraints faced.This research uses a case study approach in Dasok Village, Pamekasan Regency, East Java.Data collection through in-depth interviews. Research subjects: 1) Regent,Village Head, Inspectorate; 2) Ministry of PDTT; 3) Anti-corruption NGOs. The results showed the VFTF of Ministry PDTT was not running optimally because it was limited to receiving reports of alleged abuse of VF corruption and the lack of personnel (34 people) to monitor 75 thousand villages in Indonesia.The effort to eradicate the misuse of the VF is a challenge for JokoWidodo government in the second period (2019-2024), so the use of this grant fund can be right on a target, the village is more developed and the village community prospered.These efforts are important for the realization of good governance and for the continuation of village development.